1990
DOI: 10.1111/j.1365-2885.1990.tb00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of erythromycin in pigeons (Columba livia)

Abstract: Tissue and plasma concentrations were determined after intravenous and oral administration of erythromycin to pigeons to establish the pharmacokinetics and bioavailability of the drug. A short mean half-life of elimination of 0.9 h was found. The relative bioavailability after direct crop administration of erythromycin thiocyanate or erythromycin ethylsuccinate at a dosage rate of 100 mg/kg was less than 10%. At a drug concentration in drinking water of 1 g/l, erythromycin plasma levels were barely detectable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Pharmacokinetic studies with erythromycin in cow, guinea pig, horse, rat, foal, pigeon, and human have been carried out (6,12,16,20,22,36,37). With regard to aquatic species treated with erythromycin orally, Moffit et al (26) followed the accumulation and depletion of erythromycin thiocyanate in Chinook salmon (Oncorhynchus tshawytscha) and found that the drug was not detectable in the fish muscle 10 days after the last erythromycin feeding (using the same dosage as in our study, i.e., 100 mg kg Ϫ1 trout body weight day Ϫ1 for 21 days).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies with erythromycin in cow, guinea pig, horse, rat, foal, pigeon, and human have been carried out (6,12,16,20,22,36,37). With regard to aquatic species treated with erythromycin orally, Moffit et al (26) followed the accumulation and depletion of erythromycin thiocyanate in Chinook salmon (Oncorhynchus tshawytscha) and found that the drug was not detectable in the fish muscle 10 days after the last erythromycin feeding (using the same dosage as in our study, i.e., 100 mg kg Ϫ1 trout body weight day Ϫ1 for 21 days).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a common "pioneer" used in the research about the bio-films [1]. It was found that Pseudomonas cells adhere to stainless steel walls after 30 seconds of exposure [2].…”
Section: Introductionmentioning
confidence: 99%